Chemical and Physical Treatments of Four Rattan Species after Felling - Djamal Sanusi (Masyarakat Peneliti Kayu Indonesia, 2012)
The effectiveness of chemical and physical treatments in protecting four rattan species (i.e., batang, saloso, lambang, anranga) against blue stain attack were studied. Four rattan mature stem of each species were felled, and each rattan cane was cutted into 9 samples with 1 m long for every treatment. The treatments consisted of soaking in 0.5% formalin solution for 10 min, soaking in 10% boric acid solution for 10 min, and dipping the two cross sections in melted wax. Untreated samples were also prepared for control. The samples were stored in harvesting location for 20 days. Every 5 days, the samples were observed for the presence of blue stain attack. The results showed that untreated samples were attacked by blue stain with the average intensity of 59.3% and the average depth of 5.3 cm. Samples soaked in 0.5% formalin solution were attacked by blue stain with the average intensity of 40.3% and the average depth of 2.4 cm. Samples soaked in 10% boric acid were attacked by blue stain with the average intensity of 18.8% and the average depth of 0.8 cm. Samples treated by melted wax were found to be free from blue stain attack.Key words: blue stain, chemical treatment, physical treatment, rattan